The Role of Principals in Improving Teachers' Pedagogic Competence through Continuous Professional Development Programs - Muhammad Mamduh Nuruddin; Taufik; Muchammad Ibnu Muzakir; Mukhlisin (Edukasiana: Journal of Islamic Education, 2025)
This study aims to analyze the application of school principals' policies in improving the pedagogic competence of teachers in Darunnajah Islamic Boarding School. The research method used is qualitative with a case study approach, which collects data through in-depth interviews with principals, vice principals, and teachers, as well as observation of policy planning and evaluation activities. The data obtained were analyzed using thematic analysis techniques to identify key themes related to policy planning, evaluation, and collaboration in improving pedagogic competence. The results of the study show that the policies implemented by the principal at the Darunnajah Islamic Boarding School focus on structured planning, continuous evaluation, and collaboration with teachers. Systematic planning and regular evaluation have been proven to increase teaching effectiveness. In addition, collaboration between school principals and teachers in designing education policies also strengthens the implementation of policies that are relevant to educational needs. Nonetheless, challenges in implementation such as resistance to change and resource limitations remain obstacles. This research contributes to understanding the importance of inclusive and continuous evaluation-based education policies to improve the pedagogic competence of teachers in Islamic boarding schools